Pengaruh Penerapan Model Pembelajaran Learning Cycle 5E Terhadap Kompetensi Belajar Peserta Didik Tentang Materi Sistem Gerak Kelas XI MIPA SMA Pertiwi 1 Padang - Ella . Azzani (Program Studi Pendidikan Biologi Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Raden Fatah Palembang, 2020)
ABSTRACT The problem at SMA Pertiwi 1 Padang is the low level of student learning competencies which includes aspects of knowledge, attitudes, and skills. Efforts that can be done are applying the LC 5E learning model on ecological material at Solok Selatan 5 High School. This type of research is a semi-experimental research design, namely the Randomized Control-Group Posttest Only Design. The population in the study of all students of class XI MIPA SMAN Pertiwi 1Padang who were enrolled in the 2019/2020 Academic Year amounted to 82 people grouped in four classes. Sampling used purposive sampling technique, class XI 2MIPA as experimental class and class XI 3 MIPA as experimental class control. Instruments in the form of posttest questions for knowledge competencies, observation sheets for attitude competencies and product assessment for skills competencies. Based on the results of the study using the t-test on the competency of students' knowledge the value of tcount was 3,02>1,67 t table, and the competency skill was tcount 3,67>1,67 t table. In the attitude competence of the experimental class 83% are good categories while the control class is 72% with sufficient categories. This shows that the hypothesis is accepted in the competence of knowledge, attitudes and skills. The conclusion of the study is that the LC 5E learning model has a positive effect on students' learning competencies in ecological material at SMA Pertiwi 1 Padang. Keywords: Learning Cycle 5E, Learning Competencies